2017
DOI: 10.1007/s12035-017-0530-6
|View full text |Cite
|
Sign up to set email alerts
|

Viruses and Multiple Sclerosis: From Mechanisms and Pathways to Translational Research Opportunities

Abstract: Viruses are directly or indirectly implicated in multiple sclerosis (MS). Here, we review the evidence on the virus-related pathophysiology of MS, introduce common experimental models, and explore the ways in which viruses cause demyelination. By emphasizing knowledge gaps, we highlight future research directions for effective MS diagnostics and therapies: (i) identifying biomarkers for at-risk individuals, (ii) searching for direct evidence of specific causative viruses, (iii) establishing the contribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 116 publications
1
9
0
7
Order By: Relevance
“…Similar interaction with HLA has previously been reported for immune response to EBV (19). How these interactions fit with the previously suggested mechanisms for how viruses can trigger autoimmunity, like molecular mimicry and bystander activation (55,56), as well as interactions with other viruses not studied here (57,58), remains to be determined and the present study adds to the complexity regarding the specificity explained by these mechanisms.…”
Section: Discussionsupporting
confidence: 87%
“…Similar interaction with HLA has previously been reported for immune response to EBV (19). How these interactions fit with the previously suggested mechanisms for how viruses can trigger autoimmunity, like molecular mimicry and bystander activation (55,56), as well as interactions with other viruses not studied here (57,58), remains to be determined and the present study adds to the complexity regarding the specificity explained by these mechanisms.…”
Section: Discussionsupporting
confidence: 87%
“…However, the clinical relevance-with respect to whether these alterations contribute towards susceptibility for MS or, instead, they exert a relative protective effect-remains controversial both for adult [53,54] and pediatric populations [55,56]. In 2016, two case control studies reported distinct patterns of gut microbiota composition by the use of 16S ribosomal ribonucleic acid rRNA metagenomics analysis [57,58] (for further discussion on the potential of metagenomic techniques as applied to MS, see [59,60]). These studies provided evidence of reduced diversity in the gut microbiome of MS patients compared to controls.…”
Section: Mechanisms Of Immune-modulation By Intestinal Microbiota-climentioning
confidence: 99%
“…MS is a complex autoimmune disease with clinical variability. As such, the establishment of a causative role for intestinal microbiota towards disease pathogenesis requires combined efforts from the field of metagenomics and other "-omics" approaches [59,60,111] with the capacity for high throughput data production and the application of these data in the context of translational medicine.…”
Section: Conclusion: Treat the Microbiome-treat Ms?mentioning
confidence: 99%
“…The potential of SARS-CoV-2 for direct CNS invasion poses a special challenge for MS. Coronaviruses have been previously shown to invade the CNS (reviewed in [ 51 , 52 ]) and to induce direct neuron loss [ 34 ]. A similar potential for SARS-CoV-2 remains to be elucidated; however, if proven, it would suggest that COVID-19 in the context of MS further predisposes PwMS towards neurodegeneration, a pathological component also recognized early in the course of the disease.…”
Section: Covid-19 and Ms Comorbidities That Affect Ms Prognosis mentioning
confidence: 99%